Turnover and Natal Dispersal in the Finnish Golden Eagle (Aquila chrysaetos) Population - Aure Kylmänen; Ekaterina Karabanina; Tuomo Ollila; Suvi Ponnikas; Laura Kvist (Diversity, 2023)
Estimating turnover in a population provides information on population dynamics, such as dispersal and mortality. Dispersal increases genetic diversity and affects the genetic structure. Golden eagles are monogamous, tend to mate for life, and have strong nest site fidelity, which suggests low turnover rates. Here, we first studied genetic diversity and population structure in the Finnish golden eagle population using 11 microsatellite loci and a fragment of a mitochondrial DNA control region. We found no notable changes in genetic diversity during the 15-year study period and did not discover any population structure. Then, we examined the turnover rate using chick genotypes (N = 935) by estimating relatedness between chicks born in the same territory in different years. The results showed a turnover rate of 23%, which correlated with the breeding success of the previous year. Similarly, in the absence of turnover, the pair changed nest sites within a territory after an unsuccessful breeding. In addition, our dataset also revealed natal dispersal of ten individuals. Natal dispersal distance was 110 km on average (median 98 km); however, the distance seemed to vary depending on geographical location, being greater in Northern Finland than in Southern Finland.